The Role of Opportunity to Learn on Student Mathematics Anxiety, Problem-Solving Performance, and Mathematics Performance - Guo, Siwen; Liao, Shanhui (Frontiers in Psychology, 2022)
This study examined the effects of opportunity to learn (OTL) or the content coverage in mathematics on student mathematics anxiety, problem-solving performance and mathematics performance. The pathways examining the influences of OTL on student problem-solving performance and mathematics performance via mathematics anxiety were also tested. A sample of 1,676 students from Shanghai-China, and a sample of 1,511 students from the United States (US) who participated in Programme for International Student Assessment (PISA) 2012 were used for the analyses. The results from multilevel models and path models supported our hypotheses that OTL not only showed significant direct effects on student mathematics anxiety, problem-solving performance, and mathematics performance, but also presented indirect effects on student problem-solving performance and mathematics performance via mathematics anxiety in both Shanghai-China and US, controlling for student gender, grade, and socioeconomic status. The practical implications of the current results were also discussed.